Enhancing construction safety education : Insights from student perspectives - Alhammadi, Yasir; M. Farouk, Abdelrahman; Rahimi, A. Rahman (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Construction safety education is crucial as it ensures worker well-being, improves construction quality, and contributes to sustainable infrastructure development and safeguarding lives. This study aims to examine students’ perceptions of construction safety education. A structured questionnaire survey aligned with the National Examination Board in Occupational Safety and Health (NEBOSH) safety topics was used to collect data from students on their understanding of construction safety topics (CSTs). Data were gathered from 161 students and analyzed using Cronbach’s alpha, mean calculations, standard deviation measurements, normalization value, Kruskal–Wallis tests, and correlation analysis. The findings reveal a strong awareness and interest in fire safety, with variations across engineering faculties, academic years, and specific topics, suggesting the need for tailored educational strategies to improve construction safety knowledge and align education with industry needs. This study represents the first investigation into students’ comprehension of CSTs in Saudi Arabia. The study insights can guide decisionmakers in refining existing curriculums, ensuring students develop a strong understanding of safety protocols in construction projects. By aligning education with industry requirements, policymakers can enhance the preparedness of graduates, promoting safer practices in engineering. This contributes to the overall economic and safety progress of nations.